2018
DOI: 10.1021/acs.chemrestox.8b00024
|View full text |Cite
|
Sign up to set email alerts
|

Simple Determination of Gaseous and Particulate Compounds Generated from Heated Tobacco Products

Abstract: As a new form of cigarettes, heated tobacco products (HTPs) have been rapidly distributed worldwide. In this study, an improved method for analyzing gaseous and particulate compounds generated from HTPs is described. Smoke is collected using a GF-CX572 sorbent cartridge with 300 mg of carbon molecular sieves, that is, Carboxen 572 (CX572), and a 9 mm glass-fiber filter (GF). After collection, the CX572 particles from the cartridge are transferred along with the GF and deposited into a vial containing two phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 19 publications
2
89
2
2
Order By: Relevance
“…A systematic review concluded that HTPs exposed users and bystanders to toxic substances. [33][34][35] These studies suggest the possible harmful effects of the passive smoking of HTPs. The WHO report published in July 2019, claimed that heated tobacco contains the same harmful substances as combustible cigarette and does not necessarily reduce health risks.…”
Section: Discussionmentioning
confidence: 71%
“…A systematic review concluded that HTPs exposed users and bystanders to toxic substances. [33][34][35] These studies suggest the possible harmful effects of the passive smoking of HTPs. The WHO report published in July 2019, claimed that heated tobacco contains the same harmful substances as combustible cigarette and does not necessarily reduce health risks.…”
Section: Discussionmentioning
confidence: 71%
“…The tobacco industry claims that during HTP use, emissions of toxic chemicals are reduced due to the lower working temperature of the devices [13][14][15]23,24]. The results of independent studies suggest that toxic compounds are not completely removed from the HTP aerosol and these products are still not risk-free (Table 1) [7,19,[25][26][27][28][29][30][31][32][33][34][35]. Uchiyama et al compared the chemical composition of the aerosol from all 3 available heated tobacco products: IQOS with 4 different heat sticks, glo with 3 different heat sticks, and Ploom TECH with 3 different tobacco capsules, with smoke generated from 2 different reference cigarettes [7].…”
Section: Chemical Composition Of Generated Aerosolmentioning
confidence: 99%
“…The results of independent studies suggest that toxic compounds are not completely removed from the HTP aerosol and these products are still not risk-free (Table 1) [7,19,[25][26][27][28][29][30][31][32][33][34][35]. Uchiyama et al compared the chemical composition of the aerosol from all 3 available heated tobacco products: IQOS with 4 different heat sticks, glo with 3 different heat sticks, and Ploom TECH with 3 different tobacco capsules, with smoke generated from 2 different reference cigarettes [7]. Water accounted for 75-85% of the total gaseous and particulate matter generated during IQOS and glo use, compared to 17-27% in the smoke from traditional cigarettes [7].…”
Section: Chemical Composition Of Generated Aerosolmentioning
confidence: 99%
See 2 more Smart Citations